Tribological Investigation of the Surface Protective Layer-Forming Effect of a Nano-Sized Yttria–Silica Mixture as a Lubricating Oil Additive - Ádám István Szabó; Attila Csík; Tamás Fodor; Kálmán Vad; Márk Marsicki; Álmos Dávid Tóth (Lubricants)
Nanoparticles exhibit diverse effects when added as additives to oily medium, enhancing tribological properties and surface characteristics. Studies have shown that many oxide ceramic nanoparticles improve friction and wear, while mixtures also demonstrate favorable tribological properties. This study explores the tribological effect of an yttria–silica (Y2O3, SiO2) nanoparticle mixture in a Group III base oil medium. The results reveal that the yttria–silica mixture significantly reduces friction (−8–17%), mean wear scar diameter (−32%), and wear volume (−94%), while increasing load-bearing capacity (+114%) by creating a durable boundary layer. Observations from scanning electron microscopy revealed the original surface is protected. EDX analyses highlight the boundary layer’s elemental composition, which is high in yttrium, silicon, and oxygen and found in higher areas. XRD analysis could not detect the yttria nanoparticle additive within the boundary layer, suggesting that it fragmented due to sliding stress, resulting in an amorphous structure for the new boundary layer. TEM imaging confirmed that the boundary layer thickness is 40–45 nm. These findings demonstrate significant potential for industrial applications in developing advanced, high-performance lubricants for demanding mechanical systems.